PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN ASSET TURNOVER TERHADAP HARGA SAHAM MELALUI NET PROFIT MARGIN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN FARMASI DI BURSA EFEK INDONESIA TAHUN 2018 - 2023 - Siliwangi, Fitria Faradhila; Nurdin, Nurdin; Lasmanah, Lasmanah (Worksheet : Jurnal Akuntansi, 2025)
The This study aims to analyze the effect of the Current Ratio, Debt to Equity Ratio, and Asset Turnover on Stock Prices with Net Profit Margin as an intervening variable in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. The data were obtained from IDX Statistics and the Indonesia Stock Exchange (IDX). The research population consisted of 11 companies, and after applying the purposive sampling method, 10 companies were selected as the research sample. The analytical techniques used in this study were panel data regression and the Sobel test. The results of the analysis show that simultaneously all independent variables, which consist of Current Ratio, Debt to Equity Ratio, Asset Turnover, and Net Profit Margin, have a significant effect on stock prices. Partially, the Current Ratio, Debt to Equity Ratio, and Asset Turnover variables do not have a significant effect on stock prices, while the Net Profit Margin variable has a positive and significant effect on stock prices. The results also indicate that Current Ratio, Debt to Equity Ratio, and Asset Turnover simultaneously have a significant effect on Net Profit Margin. Partially, the Current Ratio and Debt to Equity Ratio do not have a significant effect on Net Profit Margin, whereas Asset Turnover has a significant effect on Net Profit Margin. This study also examined the indirect effect of Current Ratio, Debt to Equity Ratio, and Asset Turnover on stock prices mediated by Net Profit Margin. The results of the analysis show that Current Ratio and Debt to Equity Ratio do not have an indirect effect on stock prices through Net Profit Margin. Meanwhile, Asset Turnover mediated by Net Profit Margin has a significant effect on stock prices.